Effect of Bacillus spp. as a biostimulants for Brassica oleracea var. capitata and Brassica oleracea var. sabellica microgreens - Gutiérrez-Chávez, Aldo (2025)
Introduction. The Bacillus genus has been used as a biostimulant with positive effects on crop yield and quality. However, there are few studies on its application in microgreens. Objective. To evaluate the effect of B. subtilis (BsC4 and BsPC) and B. thuringiensis (Bt24) as biostimulants on the germination and growth of red cabbage (Brassica oleracea var. capitata) and kale (B. oleracea var. sabellina) microgreens indoor. Materials and Methods. The study was conducted at the Autonomous University of Chihuahua, Mexico, in 2023. Four treatments were assessed: Bt24, BsC4, BsPC, and seedlings without microorganisms (control) on red cabbage and kale seeds, under a completely randomized design (n = 5). Germination was monitored in the first trial, and microgreens development was assessed in the secund. After 15 days, morphological variables, photosynthetic pigments, nitrate content, quality, and yield were measured. Data were analyzed using Analysis of Variance (ANOVA) and Tukey tests (p < 0.05). Results. For kale, Bt24 improved germination speed (31.17 %) and reduced germination time (4.61 %), with no significant effect on red cabbage. In kale, yield increased (62,60 %) with Bt24, particularly in fresh biomass (63.3 %) and cotyledon area (61.57 %). In cabbage, BsC4 increased yield (44.31 %) and improved fresh biomass (42.21 %) and cotyledon area (50.57 %). Nitrate content was highest in lake with BsPC (138.30 %) and in red cabbage with Bt24 (65.14 %), without exceeding safe limits. For visual quality, both crops achieved the “Good” and “Excellent” categories, with no differences between treatments. Conclusions. These results suggest that B. thuringiensis and B. subtilis could be used as growth biostimulants for cabbage and kale microgreens, offering a promising to optimize microgreen production under controlled conditions.